Digital Applications to Support Childres's Dental Health Promotion - Fitriyanti; Wartiniyati (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2024)
Background : Stunting is a world problem because stunting is a growth and development disorder in infants (0 - 11 months) and toddlers (12 - 59 months) as a result of chronic malnutrition, especially in the first thousand days of life (HPK) so that children are too short for their age. Stunting can even disrupt intelligence levels, make you more susceptible to disease, risk future declines in productivity levels, and hamper economic growth, thereby increasing poverty. Stunting cannot be treated. So the problem of stunting can be overcome, of course, through promotional and preventive means. One of the promotional efforts is the promotion of stunted children's teeth. Since stunting affects children and toddlers, the target of outreach is parents. Method : The research materials are books, articles, and other documents related to digital applications to support the health promotion of children with stunting. Searches for supporting health promotion were carried out using a manual search engine. All digital applications obtained are sorted according to research needs. Using a reference manager, namely the Mendeley application and Publish or Perish. Results: There are 10 digital applications to support the promotion of dental health in stunted children, namely: 1. Application to literacy studies; 2. Interactive presentation application; 3. Interactive learning media maker application; 4. Remote class application; 5. Group study room application; 6. Digital question practice application; 7. Book search application; 8. Language translation app; 9. Image search application; 10. Video editing application. Conclusion : The digital application supports the promotion of dental health in stunted children so that it is interesting, and memorable so that it becomes an inspiring message for mothers with dental health problems in stunted children. Keywords : Digital applications, supporting health promotion, teeth of stunted children